1987
DOI: 10.1016/0014-5793(87)80192-8
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic acetylcholine receptors in cultured neurons from the hippocampus and brain stem of the rat characterized by single channel recording

Abstract: Single channel recording techniques have been applied to neurons cultured from the hippocampus and the respiratory area of the brain stem of fetal rats in order to search for nicotinic acetylcholine receptors (nAChR) in the central nervous system. In addition to acetylcholine (ACh), the potent and specific agonist (+)-anatoxin-a was also used to characterize nicotinic channels. nAChRs were concentrated on the somal surface near the base of the apical dendrite, and in some patches their density was sufficient t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

1988
1988
2003
2003

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(19 citation statements)
references
References 30 publications
1
17
0
1
Order By: Relevance
“…Single-channel conductances of 20-50 pS have been determined for other nicotinic receptor channels in mammalian central and peripheral neurones (Aracava et al 1987;Derkach, North, Selyanko & Skok, 1987;Lipton et al 1987;Mathie et al 1987). The amplitude ratio of whole-cell current to single-channel current suggests that there are > 103 functional nicotinic receptor channels per cardiac neurone and, for an estimated surface area of 2000 ,Um2, the average channel density is -0 5 channels per /tm2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-channel conductances of 20-50 pS have been determined for other nicotinic receptor channels in mammalian central and peripheral neurones (Aracava et al 1987;Derkach, North, Selyanko & Skok, 1987;Lipton et al 1987;Mathie et al 1987). The amplitude ratio of whole-cell current to single-channel current suggests that there are > 103 functional nicotinic receptor channels per cardiac neurone and, for an estimated surface area of 2000 ,Um2, the average channel density is -0 5 channels per /tm2.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that a functional neuronal receptor channel consists of at least one ACh-binding and one non-ACh-binding subunit (Ballivet, Nef, Couturier, Rungger, Bader, Bertrand & Cooper, 1988; Papke, Boulter, Patrick & Heinemann, 1989). Electrophysiological studies of membrane currents evoked in response to exogenous ACh in mammalian cultured central and peripheral neurones provide evidence of numerous types of neuronal nicotinic receptor channels (O'Lague, Potter & Furshpan, 1978;Ogden, Gray, Colquhoun Aracava, Deshpande, Swanson, Rapoport, Wonnacott, Lunt & Albuquerque, 1987; Lipton, Aizenman & Loring, 1987; Mathie, Cull-Candy & Colquhoun, 1987). Although the pharmacological actions of ganglionic blocking agents on neurally evoked postsynaptic currents in rat parasympathetic submandibular ganglia (Ascher, Large & Rang, 1979;Rang, 1982) and amphibian parasympathetic cardiac ganglia (Hartzell et al 1977;Lipscombe & Rang, 1988) have been described, neuronal nicotinic receptor function has not been investigated extensively in isolated neurones.…”
Section: Introductionmentioning
confidence: 99%
“…Although the psychologic effects of tobacco smoking have been acknowledged for centuries (reviewed in Schalling and Waller, 1980), it was not until the late 1980s that the existence of functional nicotinic acetylcholine receptors (nAChRs) in the brain was demonstrated (Aracava et al, 1987;Lipton et al, 1988;Vidal and Changeux, 1989;Ramoa et al, 1990). Nicotinic receptors (nAChRs) are acetylcholine-gated cationic channels present in neuronal and non-neuronal cells (see Clementi et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…We have preliminary evidence that synaptosomes from nicotine-treated rats are capable of responding to other depolarizing agents, such as 10 mA4 KCI or 60 puM veratridine (Hillard and Pounds, 1991b), and so it is likely that the lack of effect of nicotine in vitro is due to insufficient sodium influx through nAChR. Patchclamp studies of CNS nAChR have shown that the amplitude of inward current activated by nicotine decreases with depolarization (Aracava et al, 1987;Mulle and Changeux, 1990), which supports the possibility that the nAChR are less likely to open following chronic nicotine treatment in vivo.…”
Section: Discussionmentioning
confidence: 99%